The Breathless Heart : Apneas in Heart Failure - Emdin, Michele; Giannoni, Alberto; Passino, Claudio (Springer International Publishing : Imprint: Springer, 2017)
This book systematically focuses on central sleep apneas, analyzing their relationship especially with heart failure and discussing recent research results and emerging treatment strategies based on feedback modulation. The opening chapters present historical background information on Cheyne-Stokes respiration (CSR), clarify terminology, and explain the mechanics and chemistry of respiration. Following a description of the physiology of respiration, the pathophysiology underlying central apneas in different disorders and particularly in heart failure is discussed. The similarities and differences of obstructive and central apneas are then considered. The book looks beyond the concept of sleep apnea to daytime CSR and periodic breathing during effort and contrasts the opposing views of CSR as a compensatory phenomenon or as detrimental to the failing heart. The diagnostic tools currently in use for the detection of CSR are thoroughly reviewed, with guidance on interpretation of findings. The book concludes by describing the various forms of treatment that are available for CSR and by explaining how to select patients for treatment.
Keywords: Medicine.; Cardiology.; Respiratory organs -- Diseases.; Neurology.; elektronické knihy; electronic books